Impact of location of inpatient cancer care on patients with Ewing sarcoma and osteosarcoma—A population‐based study. Issue 7 (15th March 2021) - Alvarez, Elysia; Malogolowkin, Marcio; Pollock, Brad H.; Li, Qian; Johnston, Emily; Marina, Neyssa; Wun, Ted; Thorpe, Steven; Keegan, Theresa
Abstract: Background: Ewing sarcoma (EWS) and osteosarcoma (OS) require multidisciplinary treatment. Care at specialized cancer centers (SCC: Children's Oncology Group affiliated and/or National Cancer Institute‐designated cancer center) has been found to improve outcomes in patients with leukemia, but studies have not considered location of care and outcomes in EWS and OS patients, an ideal group to evaluate given their specialized multidisciplinary treatment needs. Methods: Patients hospitalized with primary EWS and OS (2000–2014) were identified using the California Cancer Registry linked with hospitalization data. Patients were divided into age groups (0–18, 19–39, ≥40 years), and classified on whether they received all versus part/none of their inpatient treatment at a SCC within 1 year of diagnosis. Multivariable Cox proportional hazards regression identified factors associated with survival. Results: There were 531 ES and 959 OS patients. Five‐year overall survival was better for patients with EWS (all: 63% vs. part/none: 42%) and OS (all: 64% vs. part/none: 47%) who received all of their treatment at a SCC. After adjusting for sociodemographic and clinical factors, receiving all inpatient cancer treatment at a SCC was associated with superior overall survival (EWS HR: 0.49, CI 0.37–0.67; OS HR: 0.78, CI 0.63–0.97). Conclusion: Our results suggest that treatment for EWS and OS at a SCC is associated with significantly improved survival even after adjustment for known prognostic factors. The superior survival among those treated at SCCs may be due to having greater access to clinical trials and services at SCCs.